2006
DOI: 10.1080/02770900600710706
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization toAlternariaandCladosporiumin Patients with Respiratory Allergy and Outdoor Counts of Mold Spores in Ankara Atmosphere, Turkey

Abstract: Sensitization to Alternaria and Cladosporium has been reported to be 3% to 30% in European countries. However, in Turkey, there is limited data about the prevalence of sensitization to these molds and the intensity of the two mold spores in Ankara atmosphere. This study was designed to evaluate the sensitization to Alternaria and Cladosporium in patients with respiratory allergy in Ankara and also the concentration of the two molds in Ankara atmosphere. Allergic rhinitis and asthma patients living in Ankara we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 20 publications
2
9
0
6
Order By: Relevance
“…Outdoor mold spores are present all the year round suspended in air, but they increase during summer (21). Cladosporium and Alternaria sensitivity is reported around 10% in the literature which is compatible with our data.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Outdoor mold spores are present all the year round suspended in air, but they increase during summer (21). Cladosporium and Alternaria sensitivity is reported around 10% in the literature which is compatible with our data.…”
Section: Discussionsupporting
confidence: 82%
“…Cladosporium and Alternaria sensitivity is reported around 10% in the literature which is compatible with our data. Allergic rhinitis is common in subjects sensitive to molds (21,22). Dikensoy et al (11) had found sensitivity rates for Alternaria and Cladosporium as 48.9% and 41.8% respectively in asthmatic patients from Gaziantep.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiyolojik çalışmalarda, Alternaria sensitizasyonunun prevalansı %3,6 iken, alerjik hastalığı olan seçilmiş hastalarda %30'a kadar çıkmakta-dır (11) . Bölgemizde toplumda Alternaria prevalansını gösteren çalışma olmamasına rağmen, solunum yolu alerjisi olan hastalarda Alternaria duyarlılığını araştı-ran çalışmalar vardır ve %11,9 civarında bildirilmektedir (12) . Toplumdaki prevalansın hafif üstünde %18 oranında duyarlılık saptadığımız için kontrol grubumuzun olmamasının önemi azalmıştır.…”
Section: Discussionunclassified
“…This can be considered to be very important from the perspective of the reproduction of fungi, allergic reaction and pathogenesis (Bavbek et al, 2006;Inal et al, 2008). Spores generally speaking enter the body through the respiratory system and on occasion rarely through the digestive tract or skin.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the characteristic of being able to develop in different habitats, fungi are widely dispersed across earth (Bavbek et al, 2006;Inal et al, 2008). Some of the fungi lead a symbiotic existence whilst others can be saprophytic or parasitic (Öner, 2009).…”
Section: Introductionmentioning
confidence: 99%